Analysis of Fashion Value Chain Sustainability to Strengthen Added Value Through Entertainment Activities (Fashion Shows) syarifapd - Syarifa Priani Dewi; Sugeng Santoso (Dinasti International Journal of Management Science, 2023)
Fashion is a secondary human need that can change according to the times or someone's wishes which can be seen from language, habits to how to dress. The production of fashion products is inseparable from various value chain activities. The value chain is a collection of activities carried out by each company to design, manufacture, market, deliver, and support its product. The fashion value chain consists of design, production, marketing and distribution activities. Fashion is also a product of the creative economy which is a mainstay in the country. The potential for various fashion products in Indonesia is enormous, so it is necessary to develop various fashion products in Indonesia to strengthen their added value. This research is a quantitative study using MDS-RAPFISH analysis with a case study in Nganjuk Regency. The results of this study show that the sustainability status of the value chain in design activities, production processes and marketing shows a fairly good sustainability status. Meanwhile, the dimensions of distribution and entertainment activities show good sustainability. And the overall results of the MDS-RAPFISH show indications of improvement, except for the dimensions of marketing and entertainment activities.